Perspectives in animal phylogeny and evolution - Minelli, Alessandro (Oxford : Oxford University Press, 2009)
Animal phylogeny is undergoing a major revolution due to the availability of an increasing amount of molecular data, the application of novel methods of phylogenetic reconstruction, and advances in palaeontology and molecular developmental biology. This book revises major events in animal evolution in light of these advances.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Phylogeny; Evolution (Biology)